If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x * x + -3x + -8 = 0 Multiply x * x 4x2 + -3x + -8 = 0 Reorder the terms: -8 + -3x + 4x2 = 0 Solving -8 + -3x + 4x2 = 0 Solving for variable 'x'. Begin completing the square. Divide all terms by 4 the coefficient of the squared term: Divide each side by '4'. -2 + -0.75x + x2 = 0 Move the constant term to the right: Add '2' to each side of the equation. -2 + -0.75x + 2 + x2 = 0 + 2 Reorder the terms: -2 + 2 + -0.75x + x2 = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -0.75x + x2 = 0 + 2 -0.75x + x2 = 0 + 2 Combine like terms: 0 + 2 = 2 -0.75x + x2 = 2 The x term is -0.75x. Take half its coefficient (-0.375). Square it (0.140625) and add it to both sides. Add '0.140625' to each side of the equation. -0.75x + 0.140625 + x2 = 2 + 0.140625 Reorder the terms: 0.140625 + -0.75x + x2 = 2 + 0.140625 Combine like terms: 2 + 0.140625 = 2.140625 0.140625 + -0.75x + x2 = 2.140625 Factor a perfect square on the left side: (x + -0.375)(x + -0.375) = 2.140625 Calculate the square root of the right side: 1.463087489 Break this problem into two subproblems by setting (x + -0.375) equal to 1.463087489 and -1.463087489.Subproblem 1
x + -0.375 = 1.463087489 Simplifying x + -0.375 = 1.463087489 Reorder the terms: -0.375 + x = 1.463087489 Solving -0.375 + x = 1.463087489 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.375' to each side of the equation. -0.375 + 0.375 + x = 1.463087489 + 0.375 Combine like terms: -0.375 + 0.375 = 0.000 0.000 + x = 1.463087489 + 0.375 x = 1.463087489 + 0.375 Combine like terms: 1.463087489 + 0.375 = 1.838087489 x = 1.838087489 Simplifying x = 1.838087489Subproblem 2
x + -0.375 = -1.463087489 Simplifying x + -0.375 = -1.463087489 Reorder the terms: -0.375 + x = -1.463087489 Solving -0.375 + x = -1.463087489 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '0.375' to each side of the equation. -0.375 + 0.375 + x = -1.463087489 + 0.375 Combine like terms: -0.375 + 0.375 = 0.000 0.000 + x = -1.463087489 + 0.375 x = -1.463087489 + 0.375 Combine like terms: -1.463087489 + 0.375 = -1.088087489 x = -1.088087489 Simplifying x = -1.088087489Solution
The solution to the problem is based on the solutions from the subproblems. x = {1.838087489, -1.088087489}
| 8+6x=43+x | | 5x-5=12x-89 | | 4x+24=13x-57 | | 9x-39=3x+3 | | 6x+43=9x+13 | | -7m+46-6(m-5)=9m-(8m-3)-3m+7 | | 11x+7=9x+17 | | -7(x+6)=2x+12 | | -12p-4(3-5p)=3(p-3)-28 | | 25-4x=5x+15 | | 5-10x=41-17x | | 0.4x-8=20+0.75x | | -101-8x=9x+18 | | 4x+7=-92-7x | | 8x-4(-5x-2)=12x | | 159-5x=5x+19 | | 6x-10-3x=7x-5 | | 42x-13=42 | | -11-6x=7-9x | | 15(n+9)=3(45+5n) | | 70-3x=8x+15 | | 6x-10x+14=-2x+6 | | 3-6p-2=13 | | 2x+9=37-2x | | 6x+84=12x+12 | | -12=-6a-6a | | 4x-8+3x+27=28 | | 8x+8=6x+16 | | 4(2x-4)=7x+2 | | 4(x+9)+2=38 | | 2(x-2)+16=5x-9 | | 6y-2=-15+y |